Research on Effects of Geometry Parameters on Stability Zone of a Rotor Supported by Foil-Air Bearings Using an Improved Foil Model - Nguyen, Minh Quan; Pham, Minh Hai; Dinh, Van Phong (Old Journal, 2018)
Foil-air bearings have been drawing much scientists’ attention to application into high-speed rotating machines for environmentally friendly performance. Due to their compliant foil structure, foil-air bearings are able to resist being seized-up (because of high heat or centrifugal effect), thereby lengthening their service time. However, during working time, foil-air bearings are supposed to demonstrate their non-linear effects that need investigating, especially on rotor’s performance. In this paper, an improved foil dynamic model with bending moment included is proposed to determine the effective stiffness of foil structure. The results are compared to published experimental data. From that, influences of some geometry parameters on rotor’s stability are investigated based on a model of turbocharger with foil-air bearings.